Retraction notice to “Exposure of adult zebrafish (Danio rerio) to SARS-CoV-2 at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish” [Sci. Total Environ. 880 (2023) 163269] (Science of the Total Environment (2023) 880, (S0048969723018880), (10.1016/j.scitotenv.2023.163269)) - da Luz, Thiarlen Marinho; Guimarães, Abraão Tiago Batista; da Silva Matos, Stênio Gonçalves; de Souza, Sindoval Silva; Gomes, Alex Rodrigues; de Lima Rodrigues, Aline Sueli; Durigon, Edison Luiz; Charlie-Silva, Ives [UNESP]; Freitas, Ítalo Nascimento; Towfiqul Islam, Abu Reza Md.; Rahman, Md. Mostafizur; Silva, Abner Marcelino; et al. (Elsevier, 2025)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editor-in-Chief. Post-publication, an investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team determined that 2 of the reviews for this manuscript were fictitious. 2 review were submitted under the name of a known scientist without their knowledge. The name and fictitious contact details of the reviewers were submitted by the Corresponding Author Guilherme Malafaia during the manuscript submission process. Although the paper was reviewed by additional reviewers chosen by the Editor, this breach compromised the editorial process. The Editors-in-Chief have lost confidence in the validity/integrity of the article and its findings and have determined that it should be retracted.